Pemanfaatan Media Pembelajaran Audio Visual berbasis Aplikasi Canva - Ari Nurul Alfian; Mardi Mardi Yudhi; Rita Wahyuni Arifin; Agung Barokah; Ahmad Safei; Novan Julian (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2022)
The ability to master technology and information, especially learning media for educators in mastering the concept of learning media is very necessary. The problems faced by educators from HIMPAUDI are still not utilizing learning media in the learning process. In addition, they still don't understand how to make learning media using the Canva application. The solution to the problems above is to create learning media and learning videos using Canva. The method in implementing this Community Service activity with the main target being educators at HIMPAUDI, West Bekasi District where there are 2 resource persons, 2 moderators and 2 technical support people. PkM was held on Saturday, December 22, 2021. PkM was conducted by providing training and demonstrations to participants in using Canva applications with the support of online media in the form of zoom, YouTube and Google Drive links. The outputs of this PkM are YouTube Streaming and a draft of the BRIN Sinta Ristek Indexed PkM Journal. Keywords: Audio Visual, Canva, Learning Media, PkM Abstrak Kemampuan penguasaaan teknologi dan informasi khususnya media pembelajaran pada para Pendidik dalam penguasaan konsep media pembelajaran sangat diperlukan. Persoalan yang dihadapi para pendidik dari HIMPAUDI masih belum memanfaatkan media pembelajaran dalam proses pembelajaran. Selain itu, masih belum memahami pembuatan media pembelajaran menggunakan aplikasi canva. Solusi dari permasalahan di atas adalah membuat media pembelajaran serta video pembelajaran menggunakan Canva. Metode dalam pelaksanaan kegiatan Pengabdian kepada Masyarakat ini dengan sasaran utama adalah para Pendidik pada HIMPAUDI Kecamatan Bekasi Barat dimana terdapat 2 orang Narasumber, 2 orang Moderator dan 2 orang Techinal Support. PkM dilaksanakan pada hari Sabtu, 22 Desember 2021. PkM dilakukan dengan memberikan pelatihan dan demonstrasi kepada peserta dalam penggunaan aplikasi dari Canva dengan dukungan media online berupa zoom, YouTube dan Link Google Drive. Luaran dari PkM ini adalah Streaming YouTube dan draft Jurnal PkM Terindeks Sinta Ristek BRIN. Kata kunci: Audio Visual, Canva, Media Pembelajaran, PkM